Simulation of Routing protocol for Low power and Lossy Networks with Cooja Simulator - Nithya Lakshmi, N; Hanmandlu, M (International Journal of Computer Sciences and Engineering, 2019)
Low power and Lossy Networks now regarded as one of the most extensive study areas are comprised of a huge number of constrained nodes with restricted power, memory and processing facility. Besides, nodes in these networks consistently function on batteries and shows evidence of unpredictable communication often. Routing in such constrained networks is extremely tough since the available protocols were not suitable for low-power and lossy networks and thus the Internet Engineering Task Force (IETF) ROLL Working Group proposed an IPv6 based Routing Protocol for Low power and Lossy Networks called RPL capable of forming network routes issuing information about routing among nodes and adapting to network topologies. This paper mainly focuses on the simulation study of routing protocol for low power and lossy networks with Cooja simulator.